Clinical efficacy of ribociclib as a first-line therapy for HR-positive, advanced breast cancer. (11th February 2018) - Duso, Bruno Achutti; Trapani, Dario; Viale, Giulia; Criscitiello, Carmen; D'Amico, Paolo; Belli, Carmen; Mazzarella, Luca; Locatelli, Marzia; Minchella, Ida; Curigliano, Giuseppe
ABSTRACT: Introduction : Breast cancer (BC) remains the most frequently diagnosed cancer and the most common cause of cancer death among women of all races worldwide. Over 80% of BC cases are hormone receptor (HR)-positive, comprised of luminal A and luminal B per molecular subtypes, imposing an urgent need to fully understand the mechanisms behind progression. Ribociclib is a selective cycline-dependent kinase 4 and 6 inhibitor. A phase 1 and a phase 3 trial have established a definitive role of ribociclib as frontline in the treatment of endocrine-sensitive advanced BC. Areas covered : Herein, the authors provide an overview of the data on ribociclib covering all aspects of the drug from its pharmacokinetics to efficacy and safety. The authors also provide their perspectives for the future. Expert opinion : Ribociclib is offering an opportunity to explore a new compound at the crossroads of different molecular activity and cell targets, which focus on endocrine-resistance reversal in multiple settings including early BC. Moreover, its activity against different subtypes of BC is being studied as is its immune-modulating effect. One cautionary note is that, in a market of concomitant similar competitors, a financial discussion will be mandatory.